Improvement in Textural Properties of Mackerel (Rastrelliger kanagurta) Surimi by Using Seaweed (Sargassum tenerrimum) Extract as Natural Gel Enhancer - Shitole, Snehal S; Balange, Amjad K.; Gangan, Shardul S; Maqsood, Sajid (Journal of Meat Science, 2014)
Surimi is a Japanese term for washed fish mince which can be used as a base material for manufacturing different analogue products like shrimp, lobster, crab analogues etc. Low cost and lean fish is generally used for making surimi but its over exploitation resulted in its stock depletion recently. Dark muscle fish like mackerel can be an alternative raw material but it has low gel forming ability. An attempt has been made in the present investigation to extract phenolic compounds from seaweed (Sargassum tenerrimum) and use as cross-linker in mackerel (Rastrelliger kanagurta) surimi to enhance its gel forming ability. Seaweed extract contained total phenolic compounds of 16.24 ± 0.32 mg tannin/ gm of dry seaweed powder, added at different levels (0.5 – 2.5% of total weight of surimi) in mackerel surimi to check the effect on the properties of gels from mackerel surimi. Surimi added with 2.0% seaweed extract had the increases in gel strength by 32.45% and also lowered expressible moisture content. Decreases in whiteness (P < 0.05) and increase in pH (P > 0.05) were observed with increasing seaweed extract concentration, compared with control sample. SDS-PAGE data revealed the slight disappearance of myosin heavy chain with the incorporation of 1.5 and 2% seaweed extract in mackerel surimi gel. Thus, the seaweed extract @ 1.5 or 2% can be used as surimi gel enhancer for mackerel without affecting its sensory properties.